Key factors influencing work readiness in generation Z: A comparative study between future gen-Z workers and employer perspectives - Chayomchai, Ampol (Edelweiss Applied Science and Technology, 2025)
: This study is a mixed-methods study, with both quantitative and qualitative research. The quantitative research studies the important factors influencing the work readiness of Generation Z in Thailand. While the qualitative research studies employers in both the business and public sectors. The important variables in the study, according to the conceptual framework, are attitude, proactiveness, knowledge, intelligence skill, technology skill, learning skill, work motivation, integrity, emotional quotient, and social quotient. The data collection in the quantitative research uses questionnaires from 400 Generation Z throughout Thailand and analyzes the statistics using the partial least squares - structural equation modeling analysis. The qualitative research uses semi-structured interviews from 40 employers and analyzes the content to find conclusions. The results found that key factors influencing work readiness of Generation Z include attitude, technology skill, learning skill, work motivation, integrity, emotional quotient, and social quotient. The findings from employers revealed that five factors affecting work readiness are technology skill, learning skill, attitude, work motivation, and knowledge. When comparing research results from both students and employers, the key findings were that four factors were considered to influence work readiness included technology skill, learning skill, attitude, and work motivation.